فاعلية برنامج مقترح لتعديل الإتجاهات نحو الوعي الصحي لدى تلاميذ التعليم الثانوي - بن هدية أحمد (université d'eloud, 2026)
تهدف الدراسة إلى التحقق من فاعلية برنامج مقترح لتعديل الإتجاهات نحو الوعي الصحي لدى تلاميذ التعليم الثانوي ، حيث تم إعداد مقياس الإتجاهات نحو الوعي الصحي، ثم إعداد برنامج مقترح لتعديل الإتجاهات ،طبق على عينة تجريبية قوامها (34 فرد) وبإستخدام المنهج التجريبي وتصميم المجموعة الواحدة بتطبيق إختبار قبلي (قبل التجربة) ، ثم تطبيق البرنامج ، ثم تطبيق إختبار بعدي (بعد التجربة )، ثم تطبيق إختبار تتبعي( بعد مدة زمنية)، أسفرت النتائج على مايلي : - تحقق فاعلية البرنامج المقترح لتعديل الاتجاهات نحو الوعي الصحي لدى تلاميذ التعليم الثانوي. - إستمرارية فاعلية البرنامج المقترح لتعديل الاتجاهات نحو الوعي الصحي لدى تلاميذ التعليم الثانوي. The study aims to verify the effectiveness of a proposed program to change attitudes towards health awareness among secondary school students, where a measure of attitudes towards health awareness was prepared, and then a proposed program to modify attitudes was prepared, applied to an experimental sample of (34 individuals), using the experimental method and a single group design by applying a pre-test (before the experiment), then applying the program, then applying a post-test (after the experiment), then applying a follow-up test (after a period of time). The results resulted in the following: -To verify the effectiveness of the proposed program in changing attitudes towards health awareness among secondary school students. -The continued effectiveness of the proposed program in changing attitudes toward health awareness among secondary school students.
أطروحة دكتوراء
Keywords: إتجاهات; وعي; تلاميذ تعليم ثانوي